Implementation of Augmented Reality in Elementary School Science Education on the Solar System - Nurul Fitriyani; Peduk Rintayati; Moh Salimi (FKIP - Universitas Riau, 2026)
The limited use of learning media which are neither concrete nor interactive in elementary school science education has made it difficult for students to understand abstract concepts and has reduced their motivation. The purpose of this study is to describe the application of Augmented Reality (AR) in science education. The method used was a qualitative descriptive approach involving five teachers as classroom observers, employing observation and documentation techniques analyzed using the Miles and Huberman model. The results showed that the implementation of AR across all stages of learning fell into the “good” and “very good” categories. The five stages achieved the following scores: planning (96%), student preparation (90%), classroom implementation (91%), discussion and reflection (87%), and learning evaluation (87%). Thus, this study concludes that the implementation of Augmented Reality in IPAS learning has been carried out effectively. Future research could examine the impact and effectiveness of AR in IPAS learning quantitatively and using a wider variety of instruments.